Characterization of a novel non‐canonical splice site variant (c.886‐5T>A) in NBAS and description of the associated phenotype - Claudia S. Priglinger; Günter Rudolph; Irene Schmid; Pascale Mazzola; Tobias B. Haack; Milda Reith; Katarina Stingl; Nicole Weisschuh (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Biallelic pathogenic variants in the neuroblastoma‐amplified sequence (NBAS) gene manifest in a broad spectrum of disorders, including, but not limited to recurrent acute liver failure, skeletal dysmorphism, susceptibility to infections, and SOPH syndrome with its cardinal symptoms of short stature, optic atrophy, and Pelger–Huët anomaly. We aimed to present clinical and genetic characteristics of two sisters (20 and 15 years old) who were diagnosed with optic atrophy and cone dystrophy in childhood. Genome sequencing revealed two novel variants in NBAS in compound heterozygous state in both sisters, namely a 1‐bp deletion predicted to result in a premature termination codon (c.5104del; p.(Met1702*)), and a non‐canonical splice site variant of unclear significance (c.886‐5T>A; p.?). Results Clinical examination and history revealed cone dystrophy, optic atrophy, and Pelger–Huët anomaly, but no short stature, recurrent acute liver failure, or susceptibility to infections. RNA analysis revealed that the c.886‐5T>A variant results in two aberrant transcripts that are predicted to lead to in frame amino acid changes in the β‐propeller region of the protein. Conclusion We hypothesize that the phenotype of our subjects, which appears to be at the end of the spectrum of NBAS‐related disorders, could be explained by residual protein function mediated by the non‐canonical splice site variant c.886‐5T>A. Our study contributes to the existing knowledge on the genotypic and phenotypic spectrum of NBAS‐related disorders.